Successful production of recombinant buckwheat cysteine-rich aspartic protease in Escherichia coli - MIRA D. MILISAVLJEVIĆ; DRAŽEN R. PAPIĆ; GORDANA S. TIMOTIJEVIĆ; VESNA R. MAKSIMOVIĆ (Journal of the Serbian Chemical Society, 2009)
Herein, the expression of recombinant cysteine-rich atypical buckwheat (Fagopyrum esculentum) aspartic protease (FeAPL1) in five Escherichia coli strains differing in their expression capabilities is presented. It was shown that the expression success depended highly on the choice of FeAPL1 fusion partner. His6-FeAPL1 was produced in large quantities as an insoluble protein localized in inclusion bodies. On the other hand, MBP-FeAPL1 was localized in both the cytoplasm and inclusion bodies in BL21 and Rosetta-gami strains. Only purified soluble MBP-FeAPL1 from Rosetta-gami cells showed proteolytic activity at pH 3.0 with BSA as the substrate. The results also indicated that FeAPL1 contained a PRO segment that had to be removed for the enzyme activity to appear. The activity of FeAPL1 produced in the Rosetta-gami strain, which enables disulfide bond formation indicated the importance of the twelve cysteine residues for correct folding and functionality.